Pengaruh Model Pembelajaran Realistic Mathematic Education (RME) Terhadap Hasil Belajar Matematika Siswa Kelas V SD - Pasinggi, Yonathan.S; Akkas, Rana Zahirah; Hakim, Abdul (Universtas Negeri Makassar, 2025)
This study aims to find out the description of mathematics learning outcomes in the operation of summing fractional numbers taught using the Realistic Mathematic Education (RME) learning model and not using the learning model. The approach used is a quantitative approach with a Quasi Experimental research design in the form of a Nonequivalent Control Group Design.The population in this study is all school residents, in particular, with a sample of 40 students in class V (VA and VB). The data analysis techniques used are descriptive analysis and independent sample t-test. So that the conclusions were obtained: (1) the learning outcomes of class V UPTD SD Negeri 35 Tajuncu Soppeng Regency who were taught with the RME learning model were in the category of very good with an average score of 87.25 compared to students who were taught with the conventional model of 74.65, (2) a significance value of 0.000 was obtained, smaller than the significance level (0.000 ≤ 0.05) which means that H1 was accepted and H0 was rejected that there was an influence of the learning modelRealistic Mathematic Education (RME) on mathematics learning outcomes in the operation of summing fractional numbers of students in grade V UPTD SD Negeri 35 Tajuncu, Soppeng Regency.